Deformation Argument under PSP Condition and Applications (Analysis in Theory and Applications, 2021)
In this paper we introduce a new deformation argument, in which $C^0$-group action and a new type of Palais-Smale condition PSP play important roles. This type of deformation results are studied in [17,21] and has many different applications [10, 11, 17, 21] et al. Typically it can be applied to nonlinear scalar field equations. We give a survey in an abstract functional setting. We also present another application to nonlinear elliptic problems in strip-like domains. Under conditions related to [5,6], we show the existence of infinitely many solutions. This extends the results in [8].